Let f: R → R and g: R → R be defined by f(x) = x2 and g(x) = x + 1. Show that fog ≠ gof.

Asked by Sakshi | 1 year ago |  79

##### Solution :-

Given f: R → R and g: R → R.

So, the domains of f and g are the same.

Consider (fog) (x) = f (g (x))

= f (x + 1) = (x + 1)2

= x+ 1 + 2x

Again consider (gof) (x) = g (f (x))

= g (x2) = x+ 1

So, fog ≠ gof

Answered by Aaryan | 1 year ago

### Related Questions

#### Let A be the set of first five natural and let R be a relation on A defined as follows: (x, y) R x ≤ y

Let A be the set of first five natural and let R be a relation on A defined as follows: (x, y) R x ≤ y

Express R and R-1 as sets of ordered pairs. Determine also

(i) the domain of R‑1

(ii) The Range of R.

#### A function f: R → R is defined as f(x) = x3 + 4. Is it a bijection or not? In case it is a bijection, find f−1 (3).

A function f: R → R is defined as f(x) = x3 + 4. Is it a bijection or not? In case it is a bijection, find f−1 (3).

#### If f: R → R be defined by f(x) = x3 −3, then prove that f−1 exists and find a formula for f−1.

If f: R → R be defined by f(x) = x3 −3, then prove that f−1 exists and find a formula for f−1. Hence, find f−1 (24) and f−1 (5).

#### Consider f: R+ → [−5, ∞) given by f(x) = 9x2 + 6x − 5. Show that f is invertible with f-1(x)

Consider f: R+ → [−5, ∞) given by f(x) = 9x2 + 6x − 5. Show that f is invertible with f-1(x) = $$\dfrac{\sqrt{(x+6)-1}}{3}$$

#### If f(x) = (4x + 3)/ (6x – 4), x ≠ (2/3) show that fof(x) = x, for all x ≠ (2/3). What is the inverse of f?

If f(x) = $$\dfrac{ (4x + 3)}{(6x – 4)}$$, x ≠ ($$\dfrac{2}{3}$$) show that fof(x) = x, for all x ≠ ($$\dfrac{2}{3}$$). What is the inverse of f?